IMPROVEMENT DAIRY CATTLE BARN MANAGEMENT AFTER FOOT AND MOUTH DISEASE (FMD) OUTBREAK IN MEDOWO, KEDIRI - Permatasari, Dian Ayu; Raharjo, Dadik; Effendi, Mustofa Helmi; Budiarto, Budiarto (Universitas Airlangga, 2025)
The Foot and Mouth Disease (FMD) outbreak that began in 2022 caused significant losses for dairy farmers in Medowo Village, Kandangan District, Kediri Regency—impacting both livestock health and farmers' economic stability. To address these impacts, a community service program was carried out to improve farmers' knowledge and skills in dairy cattle housing management and biosecurity implementation. The program included training sessions, educational outreach, and technical assistance for 31 farmers from KUD Kertajaya. Evaluation was conducted through pre-test and post-test instruments to measure the effectiveness of the intervention. Pre-test results showed that only 6.5% of participants were in the